Kant on the Political Obligation of Philosophers: Reading the Secret Article in Toward Perpetual Peace. - ZHAO, YUFEI (Filozofia, 2025)
This paper offers an interpretive framework for understanding Kant's "secret article" in Toward Perpetual Peace as contributing to a three-step transition toward a republican constitution. First, rulers permit philosophers to speak freely and publicly and learn from them in secret. Second, rulers extend this freedom of public reason to all citizens, reflecting Kant's enlightenment ideal in "What Is Enlightenment?" Third, rulers relinquish legislative power, allowing the public to become the de facto legislator--thus separating executive and legislative powers, which is essential to republican government. This reading reveals that Kant's view of the relationship between philosophy and politics differs significantly from those of Plato and Machiavelli. He rejects both the Platonic philosopher-king and Machiavelli's secret advisor model. Instead, Kant sees philosophers as agents of enlightenment whose influence lies not in ruling or advising rulers, but in preparing conditions necessary for perpetual peace.